2016
DOI: 10.21276/bpr.2016.6.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antibacterial Activities of Allium Sativum and Allium Cepa

Abstract: Garlic and onion have been used widely as common household spices from the ancient period and have also been regarded as traditional healers. This study was designed to evaluate the antioxidant and antibacterial activities of fresh extracts of garlic and onion. Activities of enzymatic antioxidants (superoxide dismutase and catalase) and non-enzymatic antioxidant (ascorbic acid content) activities were measured and compared in between garlic and onion extracts. Superoxide dismutase and catalase activities in ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Many studies have shown evidence of a significant reduction of the risk of developing chronic diseases (e.g., cardiovascular, cancer, obesity, diabetes, high blood pressure, platelet aggregation, cholesterol lowering) associated with garlic consumption [1,2,3,4,5]. Together with therapeutic functions, garlic possesses additional biological activities such as antibacterial, antifungal, and antioxidant properties [6,7,8], resulting in garlic being one of the most important vegetables worldwide [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown evidence of a significant reduction of the risk of developing chronic diseases (e.g., cardiovascular, cancer, obesity, diabetes, high blood pressure, platelet aggregation, cholesterol lowering) associated with garlic consumption [1,2,3,4,5]. Together with therapeutic functions, garlic possesses additional biological activities such as antibacterial, antifungal, and antioxidant properties [6,7,8], resulting in garlic being one of the most important vegetables worldwide [9].…”
Section: Introductionmentioning
confidence: 99%
“…Shallots (Allium cepa L.) contain many phytochemical compounds, most of which are hydrocarbons and their derivatives (Griffiths et al, 2002). Quercetin and allicin are the main components of shallots that act as antimicrobials, especially antibacterials (Shrestha et al, 2016), quercetin is bound to the bacterial enzyme DNA gyrase and allicin inhibits enzymes that contain thiol (Ankri & Mirelman, 1999). DNA gyrase is an essential bacterial enzyme that catalyzes ATP-dependent negative super-coiling of double-stranded closed-circular DNA, which is included in the topoisomerase enzyme group (Reece & Maxwell, 1991) (Papillon et al, 2013).…”
Section: C-c+ T1 T2mentioning
confidence: 99%
“…Garlic (Allium sativum) also contains many phytochemical compounds that have pharmaceutical effects, including allicin which is the most potent compound as an antibacterial agent (Shrestha et al, 2016).…”
Section: C-c+ T1 T2mentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effects associated garlic may be due in part to sulfur-containing compounds such as allicine, diallyl disulfide, diallyl trisulfide that react with thiol groups of various enzymes which are critical for microorganism surveillance [164]. Spyridon et al [165] reviewed the Pharmacological effects of Allium hirtifolium and found Zinc of considereable amounts while Reyhaneh [166] determined the chemical composition and reported a vitamin C content of 31mg. Deepak et al [167] indicated that garlic extracts singly had a greater potency than 1% chloramphenicol producing significant susceptibility manifested by inhibition zone of 51 ± 0.19 mm towards B. cereus and 37 ± 0.17mm on S. aureus E. coli (34 ± 0.48).…”
Section: Garlic (Allium Sativum)mentioning
confidence: 99%